Purchase decision and purchase delay of hedonic and utilitarian products in the face of time pressure and multiplicity of options. Issue 2 (28th February 2019) - Basso, Kenny; Duschitz, Caroline da Costa; Giacomazzi, Cassandra Marcon; Sonego, Monique; Rossi, Carlos Alberto Vargas; Reck, Danúbia
Abstract : Purpose: Time pressure may change how people behave. The multiplicity of options and the nature of the products, hedonic or utilitarian, might increase the complexity of the choice and alter the effects of time pressure. Combining both factors, the purpose of this paper is to verify the moderating role played by the nature of the products observing the relationship between interaction (time pressure × multiplicity of options) and choice delay. Design/methodology/approach: A two-level factorial experimental design was applied (time pressure: with; without) × 2 (number of alternatives: two; six) × 2 (type of purchase: hedonic; utilitarian), with mixed design, considering the purchase delay a dependent variable. Findings: The results signal that the nature of the products moderates the effects of the interaction between time pressure and choice overload in purchase delay. Utilitarian purchases are more susceptible to the effects of time pressure and options overload than hedonic purchases. Originality/value: The interaction between time pressure and choice overload, researched in previous works, influences in different ways the purchase of utilitarian or hedonic products. This differentiation, taking into consideration the type of product, brings new perspectives on the purchase decision process and provides theoretical and practical information on the effects of information overload and time pressure over the consumer decision-making process.